Social Values of Early Children in The Main Character of Early Childhood: Gotong Royong - Nurbaiti, Amalia; Wachid Bambang Suharto, Abdul (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study examines the social value of the main character's fairy tales of early childhood. The purpose of this study is to find, analyze, and describe the social values ​​contained in the Tale of the Main Characters of Early Childhood: Gotong Royong. This research uses a descriptive analysis method where the focus of the research is library research. This study uses data collection documentation with the method of reading and note-taking. The data analysis technique of this research was carried out by reducing data, presenting data, verifying and drawing conclusions. The results showed that the social value of early childhood in the Tale of the Main Character of Early Childhood: Gotong Royong consists of the social value of helping, the social value of cooperation, the social value of being loyal to friends, and the social value of motivating. The social value of helping to help is related to helping people who are in trouble, whereas in this fairy tale the social value of helping is found in the stories